2014
DOI: 10.1111/pme.12359
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of X-Ray Imaging Combined with Skin Stimulation Potential-Guided Percutaneous Radiofrequency Thermocoagulation of the Gasserian Ganglion for Treatment of Trigeminal Neuralgia

Abstract: Using skin stimulation potential-guided puncture may enable more accurate microscopic adjustment of the targets localization damaged by radiofrequency and significantly enhanced clinical efficacy in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
0
22
2
Order By: Relevance
“…In addition, information on temperature used for CRF for V1 TN was not mentioned in some reports. [ 29 , 30 ] Some study was not standard and unreasonable in design reviewed by Akram et al [ 31 ] After 90 °C CRF for TN of various divisions, including V1, Nie et al [ 9 ] found facial numbness in 93.3% (28/30) of patients, but did not report eye complications. So, to reduce or prevent eye complications, we used 62 °C CRF for V1 TN.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, information on temperature used for CRF for V1 TN was not mentioned in some reports. [ 29 , 30 ] Some study was not standard and unreasonable in design reviewed by Akram et al [ 31 ] After 90 °C CRF for TN of various divisions, including V1, Nie et al [ 9 ] found facial numbness in 93.3% (28/30) of patients, but did not report eye complications. So, to reduce or prevent eye complications, we used 62 °C CRF for V1 TN.…”
Section: Discussionmentioning
confidence: 99%
“…[16,38] This finding indicates that RFT at temperatures >75°C may increase the risk of masticatory atonia. Meanwhile, the rate of masticatory atonia was only 4.8% at 68°C, which was far lower than that after RFT at a higher temperature and is consistent with that reported by Wael, [22] who performed RFT at 60°C to 70°C.…”
Section: Discussionmentioning
confidence: 98%
“…The use of X-ray to guide puncture of the FO is a common clinical practice. [ 23 ] However, Gerber [ 24 ] indicated that even with appropriate positioning of the head it is challenging to identify the FO in some patients. Neuronavigation-guided RFT with CT images has gained popularity in recent years.…”
Section: Discussionmentioning
confidence: 99%